A marginal Jew. Rethinking the historical Jesus. Vol. 4: Law and love - Meier, John P. 1942- (New Haven, CT Yale University Press, 2009)
John Meier’s previous volumes in the acclaimed series A Marginal Jew are founded upon the notion that while solid historical information about Jesus is quite limited, people of different faiths can nevertheless arrive at a consensus on fundamental historical facts of his life. In this eagerly anticipated fourth volume in the series, Meier approaches a fresh topic-the teachings of the historical Jesus concerning Mosaic Law and morality-with the same rigor, thoroughness, accuracy, and insightfulness on display in his earlier works.After correcting misconceptions about Mosaic Law in Jesus’ time, this volume addresses the teachings of Jesus on major legal topics like divorce, oaths, the Sabbath, purity rules, and the various love commandments in the Gospels. What emerges from Meier’s research is a profile of a complicated first-century Palestinian Jew who, far from seeking to abolish the Law, was deeply engaged in debates about its observance. Only by embracing this portrait of the historical Jesus grappling with questions of the Torah do we avoid the common mistake of constructing Christian moral theology under the guise of studying “Jesus and the Law,” the author concludes
Frontmatter -- -- Contents -- -- Acknowledgments -- -- Introduction to Volume Four -- -- Chapter 31. Jesus an the Law—But What is the Law? -- -- Chapter 32. Jesus’ Teaching On Divorce -- -- Chapter 33. The Prohibition of Oaths -- -- Chapter 34. Jesus and the Sabbath -- -- Chapter 35. Jesus and Purity Laws -- -- Chapter 36. Widening the Focus: The Love Commandments of Jesus -- -- Conclusion to Volume Four -- -- Maps -- -- List of Abbreviations -- -- Scripture and Other Ancient Writings Index -- -- Author Index -- -- Subject Index
Online-Ausg.
Mode of access: Internet via World Wide Web.
In English
Keywords: Jews -- Palestine